Water quality modelling and management of nitrogenous compounds in a data scarce environment - Mahlathi, Christopher Dumisani (Stellenbosch : Stellenbosch University, 2025)
Mahlathi, C. D. 2025. Water Quality Modelling and Management of Nitrogenous Compounds in a Data Scarce Environment. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/635024cd-320f-4760-add2-588c94fd6932